Adaptive upregulation of DNA repair genes following benzo(a)pyrene diol epoxide protects against cell death at the expense of mutations. Issue 22 (30th September 2016) - Christmann, Markus; Boisseau, Catherine; Kitzinger, Rebekka; Berac, Christian; Allmann, Sebastian; Sommer, Tina; Aasland, Dorthe; Kaina, Bernd; Tomicic, Maja T.
Abstract: A coordinated and faithful DNA damage response is of central importance for maintaining genomic integrity and survival. Here, we show that exposure of human cells to benzo(a)pyrene 9, 10-diol-7, 8-epoxide (BPDE), the active metabolite of benzo(a)pyrene (B(a)P), which represents a most important carcinogen formed during food preparation at high temperature, smoking and by incomplete combustion processes, causes a prompt and sustained upregulation of the DNA repair genes DDB2, XPC, XPF, XPG and POLH. Induction of these repair factors on RNA and protein level enhanced the removal of BPDE adducts from DNA and protected cells against subsequent BPDE exposure. However, through the induction of POLH the mutation frequency in the surviving cells was enhanced. Activation of these adaptive DNA repair genes was also observed upon B(a)P treatment of MCF7 cells and in buccal cells of human volunteers after cigarette smoking. Our data provide a rational basis for an adaptive response to polycyclic aromatic hydrocarbons, which occurs however at the expense of mutations that may drive cancer formation.